Differential Expression of BCL2 and IGFBP2 in Childhood Immune Thrombocytopenic Purpura Clinical Subtypes: Implications for Predicting Disease Progression and Apoptotic Regulation - Bakr, Salwa; Dash, Hanaa El; Youssef, Asmaa Ahmed Ali; El‐Hamid, Rehab Galal Abd (Pediatric blood & cancer, 2025)
ABSTRACT Background Immune thrombocytopenic purpura (ITP), which poses challenges in treatment response, is an autoimmune‐mediated bleeding disorder with an extremely complex pathogenesis and unpredictable clinical progression. Dysregulation of apoptotic pathways may influence both the pathogenesis and prognosis of ITP. This study aimed to evaluate the expression patterns of the apoptotic protein insulin‐like growth factor‐binding protein 2 (IGFBP2) and the anti‐apoptotic protein B‐cell lymphoma 2 (BCL2) as potential predictive or prognostic biomarkers for disease progression in childhood ITP. Patients and Methods The expression levels of BCL2 and IGFBP2 were assessed in peripheral blood samples from 40 pediatric ITP patients and 30 age‐ and sex‐matched healthy controls using enzyme‐linked immunosorbent assays. Results Plasma levels of BCL2 and IGFBP2 were higher in ITP patients than in control subjects. Although the difference in IGFBP2 expression was not statistically significant (p = 0.910), BCL2 expression was significantly elevated (p < 0.001). Notably, chronic ITP patients had significantly lower levels of both IGFBP2 and BCL2 markers compared to patients who achieved spontaneous recovery (p < 0.001). Conclusion BCL2 and IGFBP2 appear to be promising noninvasive biomarkers for predicting disease outcomes in newly diagnosed ITP, emphasizing the need for validation in large‐scale, multicenter longitudinal studies.